A Review of Topological Semimetal Phases in Photonic Artificial Microstructures - Xie, Boyang; Liu, Hui; Wang, Haonan; Cheng, Hua; Tian, Jianguo; Chen, Shuqi (Frontiers in Physics, 2021)
In the past few years, the concept of topological matter has inspired considerable research in broad areas of physics. In particular, photonic artificial microstructures like photonic crystals and metamaterials provide a unique platform to investigate topologically nontrivial physics in spin-1 electromagnetic fields. Three-dimensional (3D) topological semimetal band structures, which carry nontrivial topological charges, are fundamental in 3D topological physics. Here, we review recent progress in understanding 3D photonic topological semimetal phases and various approaches for realizing them, especially with photonic crystals or metamaterials. We review topological gapless band structures and topological surface states aroused from the nontrivial bulk topology. Weyl points, 3D Dirac points, nodal lines and surfaces of different types are discussed. We also demonstrate their application in coupling spin polarized electromagnetic waves, anomalous reflection, vortex beams generation, bulk transport and non-Hermitian effects.